Design and experimental evaluation of an inchworm motor driven by bender-type piezoelectric actuators. (1st November 2022) - Han, Shuo; Li, Zhi; Xu, Yunlang; Yang, Xiaofeng
Abstract: Piezoelectric actuators (PEAs) are widely used in ultra-precision detection platforms where nano-precision and non-magnetic features are required. With the development of the semiconductor industry, actuators develop toward the tendency of smaller size, higher precision, and longer travel. However, these demands are difficult to meet merely by virtue of a single piezoelectric actuator or a simple structured inchworm piezo motor, which makes it necessary to develop a new drive mode following a different drive principle. In this paper, a novel inchworm piezo motor with bender-type PEAs in phalanx distribution was proposed, which facilitates in reducing the dimension of the motor and enhances the performance and stability of the piezo motor. For the purpose of accommodating the bender-type PEAs and providing the preloads to the bender-type PEAs, a flexible mechanism housing was designed and the modal analysis was finished, avoid resonance and reduce structural vibration. Experimental results show that the resolution of the developed motor is 2 nm or less under the laser interference with an adoption rate of 10 MHz and a resolution of 0.1 nm, while the maximum stroke is over 19 mm at the constant speed of 2.3 mm s −1, and the maximum output force is 41.6 N.